The Effect of Affective Organizational Commitment Towards Innovation Capability and Its Impact To Job Performance in Family Business - Wibowo, Yohana Cahya; Christiani, Natalia (Universitas Ciputra Surabaya, 2020)
The purpose of this research is to find out about the effect of affective organizational commitment towards innovation capability and its impact to job performance in family business. Methodology – the original data was taken through an online questionnaire with 100 respondents who are members of Family Business Community in Universitas Ciputra along with the non-members. The SmartPLS 3.0 Statistics Program was used to test the proposed model. Findings– Result shows that affective organizational commitment significantly affects innovation capability and job performance and innovation capability significantly affects job performance.